KRITIK TERHADAP FORMALISME HUKUM - Risydam Bashier (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2023)
This journal examines the resistance to the Legal Formalism School which alludes to it from the point of view of basic reports. This legal critique incorporates liberal, radical, and postmodernist ideas as well as Marxist ideas. The background is legal certainty, both those that guarantee the fulfillment of laws that do not require overlapping rules or justice for the formation of laws. This journal aims to briefly familiarize readers with concepts in critical legal studies from various legal perspectives. In addition, for good journal results, the author must convey the goals and context of the development of Indonesian law. This writing uses content analysis research, which is a comprehensive discussion of critical legal studies. The results of the discussion show that the goal of the critical legal study movement to unite various legal perspectives is the main principle of Critical Legal Studies which continues to develop in Indonesia. Because of this legal aspect, recent legal developments in Indonesia are still relatively new. Some formal legal activists use the history of the Critical Legal Studies Movement to understand oppressive legal structures and policies. Therefore, criticism of legal formalism is supported by the fact that several applications are needed, both in terms of themes and movement strategies, as support for the fulfillment of legal formalism from various prevailing legal ideologies.